PENGAWASAN TEMPAT PENGELOLAAN MAKANAN DAN MINUMAN OLEH DINAS KESEHATAN DI KOTA PEKANBARU - Atika Syafitri; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pekanbaru is a metropolitan city which has a number of citizen. Because of the large number of citizenship, food and beverage which consumed by citizen arouse in types and numbers. The increasing types and numbers of food and beverage effected the increasing the food and beverage management in the whole city. Those situations above required government to show concern of healthiness and feasibility aspect of food and beverage that consumed by citizen. Therefore, there is an urge to control the food and beverage which regulated in Undang Undang Nomor 36 Tahun 2009 tentang kesehatan bab 6 upaya kesehatan pasal 109 tentang pengamanan makanan dan minuman.This research using descriptive qualitative method. Manullang controlling theory used to determine standard, conducting measurement, and making improvement. Observation, interview and documentation were used as a technique from qualitative descriptive analysis.This research shows that controlling of food and beverage by Dinas Kesehatan at Kota Pekanbaru needs an improvement. That was caused by lack of guidance for businessmen and indecisive law consequences. In order to maximizing the controlling of food and beverage management, socializing guidance to businessman and giving consistent consequences by law should be initiated.Keywords: controlling, food and beverage management, Dinas Kesehatan